2015
DOI: 10.1111/pce.12539
|View full text |Cite
|
Sign up to set email alerts
|

FcWRKY70, a WRKY protein of Fortunella crassifolia, functions in drought tolerance and modulates putrescine synthesis by regulating arginine decarboxylase gene

Abstract: WRKY comprises a large family of transcription factors in plants, but most WRKY members are still poorly understood. In this study, we report functional characterization of a Group III WRKY gene (FcWRKY70) from Fortunella crassifolia. FcWRKY70 was greatly induced by drought and abscisic acid, but slightly or negligibly by salt and cold. Overexpression of FcWRKY70 in tobacco (Nicotiana nudicaulis) and lemon (Citrus lemon) conferred enhanced tolerance to dehydration and drought stresses. Transgenic tobacco and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(75 citation statements)
references
References 68 publications
1
74
0
Order By: Relevance
“…As TFs, WRKYs are usually nuclear proteins and possess transcriptional activity [33,37,38,39]. Previously, we also found that Chinese flowering cabbage BrWRKY75 was a nuclear protein with transcriptional repression activity [36].…”
Section: Resultsmentioning
confidence: 99%
“…As TFs, WRKYs are usually nuclear proteins and possess transcriptional activity [33,37,38,39]. Previously, we also found that Chinese flowering cabbage BrWRKY75 was a nuclear protein with transcriptional repression activity [36].…”
Section: Resultsmentioning
confidence: 99%
“…TaWRKY44 may act as a positive regulator in drought, salt and osmotic stress responses (Xiatian et al, ). The WRKY transcription factors, which specifically bind to cis‐acting elements, can regulate the expression of the corresponding genes, and the W‐box is mainly present in metabolism‐ and environmental stress‐related gene promoter regions (Gong et al, ; Zhou et al, ). TaWRKY33 might be involved in the interaction of the ABA signalling pathway and might be associated with abiotic stress tolerance in plants (He et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Dehydration stress was performed as described by Gong et al (2015) with slight modification. The fresh weight (FW) of the seedlings was measured every 15 min using a scale, and the percentage FW loss was determined relative to the initial weight.…”
Section: Methodsmentioning
confidence: 99%